No Association Between Suicidality and Weight Among School-Attending Adolescents in the United Arab Emirates - Ibrahim, Hania; Mahfoud, Ziyad R. (Frontiers in Psychology, 2021)
Previous data on the link between weight and suicidality is heterogenous. We aim to investigate the potential association between weight and suicidality among adolescents in the United Arab Emirates (UAE). We hypothesize that an association exists between weight and suicidality, with those at both extremes of weight suffering higher rates of suicidal ideation, planning and attempts. The 2016 UAE Global School Health Survey (GSHS) was used. Weight categories based on the World Health Organization Body Mass Index charts were generated. Suicidality measures were based on questions on suicide ideation, planning, and attempt. Univariate and multivariate binary logistic regression were used. Overall, 3.6%, 21.4% and 17.5% of students were found to be underweight, overweight, and obese respectively. In total, 492 students (14.6%) reported suicidal ideation, 397 (11.8%) reported planning, and 389 (11.4%) reported attempts within the twelve months prior to the survey. In the multivariate logistic regression, being female, older, and of lower socioeconomic status were significantly associated with increased suicidal ideation, planning and attempts. Increased parental involvement was associated with decreased suicidality. The association between weight category and suicidality did not reach statistical significance. A significant proportion of Emirati teens are under- or over-weight, with one in seven and one in nine having considered or attempted suicide respectively. However, this study finds no significant association between weight and suicide ideation, planning, or attempts. This may be due to cultural differences in weight perception. Further research into this association can aid in tailoring suicide prevention interventions.